Depressive symptoms in critically ill COVID-19 survivors and its association with physical symptoms and health-relate quality of life - Juliana Barreto de Almeida e Silva (2022)
Long-term neuropsychiatric consequences of critical illness are well known. So, it is expected that critically ill COVID-19 patients might also present several psychiatric symptoms such as depression, with inevitable negative effect on health-related quality of life (HRQoL). This study aims to identify depression symptoms in these survivors and its association with post-discharge physical symptoms and HRQOL. This cross-sectional data is part of MAPA longitudinal project with critically ill COVID-19 patients admitted into Intensive Care Medicine Department( ICMD) of CHUSJ(October 2020 to August 2021). Patients with an ICMD stay≤24h, terminal illness, major auditory loss, or inability to communicate at follow-up time were excluded. Participants were evaluated by telephone at follow-up appointment (1-2 months post-discharge), with Patient Health Questionnaire (PHQ-9) (depression) and EuroQol 5-dimension 5-level EQ-5D-5L (HRQoL). Overall, 131 patients were included (median age=62y.o.) and 21% presented depressive symptoms. Patients with depressive symptoms showed more problems of self-care, pain/discomfort and anxiety/depression. Also reported more sleep alterations, memory difficulties,dyspnea,dysphonia, dysphagia, and trouble with balance/orthostatism. These results are in line with previous studies in COVID-19 survivors, with depression being associated with physical symptoms and worse HRQoL. Thus, early screening and treatment of depression will be fundamental to optimize the patients' recovery and HRQoL.